Avaliação de métodos analíticos e comparação das normas regulamentadoras brasileira e europeia dos cosméticos destinados à proteção contra raios UV - Lima, Numbia (Universidade Federal de São Carlos, 2025)
The document addresses the evaluation of analytical methods and the comparison of Brazilian and European regulatory standards for cosmetics, particularly those intended for UV protection. The study conducts analyses of product efficacy and safety, considering the increased exposure to sunlight and its health implications. Additionally, it discusses analytical techniques, such as chromatography, used to ensure sunscreen compliance, and examines the differences between regulations RDC 600/22 and EU 1223/09, emphasizing the need for strict regulation to protect consumers.
Evaluation of analytical methods and comparison of brazilian and european regulatory standards for cosmetics intended for protection against UV radiation
Keywords: Cosméticos; Raios UV; Regulamentação; Substâncias; CIENCIAS EXATAS E DA TERRA::QUIMICA